Bambi - Albright, Hardie, 1903-1975.; King, Cammie, 1934-2010.; Behn, Peter; Sutherland, John, 1910-2001.; Winslowe, Paula, 1910-1996.; Hand, David, 1900-1986.; Walt Disney Productions; Walt Disney Studios Home Entertainment (Firm) (Burbank, CA : Walt Disney Studios Home Entertainment, 2011)
The world's most endearing animated tale about the beauty of nature and the miracle of life.
Originally produced as a motion picture in 1942.
Bonus features: introduction by Diane Disney Miller ; Inside Walt's story meetings--enhanced ed. ; DisneyPedia: Bambi's forest friends--fun and interesting facts about real forest animal ; classic DVD bonus features.
Voices: Hardie Albright, Cammie King, Peter Behn, John Sutherland, Paula Winslowe.
MPAA rating: G.
DVD, (1.33:1).
English, French or Spanish language tracks; French or Spanish subtitles; English subtitles for the deaf and hard of hearing.
Keywords: Bambi (Fictitious character) -- Juvenile drama; Deer -- Juvenile drama; Feature films; Animated films; Video recordings for the hearing impaired